Computer Vision Used to Monitor The Youth during The Pandemic Covid-19 - Salsyabila Vidia Nur Afni; Esi Putri Silmina; Irwanda Budi Pangestu (Universitas Muhammadiyah Sidoarjo, 2021)
Computer Vision is a field that studies methods for capturing numerical or symbolic information. Some of the computer vision processes are image capture, image enhancement, segmentation, feature extraction, and clarification. AI-based Computer Vision technology allows the public to carry out more optimal surveillance to deal with Covid-19. During the Covid-19 pandemic, many people have adopted new normal habits by implementing health protocols. But not a few of our people do not understand the importance of implementing health protocols. Where after this year's Eid homecoming, not a few of our people have made trips to their hometown villages. In this case, there is already a prohibition from the Government not to make the Eid homecoming trip. These communities can be at risk of transmitting the Covid-19 virus to their families in their hometowns. This study describes how Computer Vision works in helping the community to monitor travelers from the city to minimize the spread of Covid-19. The paper wa presented using the literature review method. From the description result using the literature review, it has result that computer vision technology has enormous potential in spreading countermeasures Covid-19.